Two new species of the genus Pararrhynchium de Saussure (Hymenoptera: Vespidae: Eumeninae) from northern Vietnam - Nguyen, Lien Thi Phuong (Zootaxa, 2015)
Two new species of the genus Pararrhynchium are described and figured: P. striatum sp. nov. (northern Vietnam: Hoa Binh, Ha Tinh and Thai Nguyen) and P. concavum sp. nov. (northern Vietnam: Cao Bang). A key to all known species of the genus is provided.